Modeling of the Frozen Mode Phenomenon and Its Sensitivity Using Discontinuous Galerkin Methods (Communications in Computational Physics, 2007)
We investigate the behavior and sensitivity of the frozen mode phenomenonin finite structures with anisotropic materials, including both magnetic materials andnon-normal incidence. The studies are done by using a high-order accurate discontinuous Galerkin method for solving Maxwell's equations in the time domain. We confirmthe existence of the phenomenon also in the time-domain and study carefully the impact of the finite crystal on the frozen mode. This sets the stage for a thorough studyof the robustness of the frozen mode phenomenon, resulting in guidelines for whichdesign parameters are most sensitive and acceptable tolerances.
Keywords: Discontinuous Galerkin method; Maxwell equation; photonic crystals; frozen mode.